Collective Entrepreneurship as a Means for Sustainable Community Development: A Cooperative Case Study in South Africa - Louw van der Walt (Centro de Investigaciones Comerciales e Iniciativas Académicas, 2008)
Many in rural communities in South Africa are living in poor conditions. By stimulating economic activities, this problem can be alleviated. One way to achieve this is for entrepreneurs to form cooperative alliances. Since earnings produced are returned to the member/owner and the end result is that this wealth is kept within the community. Thereby the goal of job creation and uplifting of communities are reached. This article focuses on the constraints of institutional structures and entrepreneurial skills of farmers and non-farmers in rural areas and reflects on the establishment of a cooperative as an appropriate mechanism for promoting collective entrepreneurship. The results of the cooperative two years after implementation are also discussed.